2022
DOI: 10.3389/fphys.2022.970292
|View full text |Cite
|
Sign up to set email alerts
|

The AMPK pathway in fatty liver disease

Abstract: Lipid metabolism disorders are the primary causes for the occurrence and progression of various liver diseases, including non-alcoholic fatty liver disease (NAFLD) and alcoholic fatty liver disease (AFLD) caused by a high-fat diet and ethanol. AMPK signaling pathway plays an important role in ameliorating lipid metabolism disorders. Progressive research has clarified that AMPK signal axes are involved in the prevention and reduction of liver injury. Upregulation of AMK can alleviate FLD in mice induced by alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(76 citation statements)
references
References 126 publications
1
75
0
Order By: Relevance
“…Besides being a regulatory factor for energy status and glucose metabolism, it also plays a crucial role in regulating lipid metabolism, oxidative stress, and inflammatory responses ( Green et al, 2022 ). Fang et al have shown that these mitigative effects are achieved by activation of the Nrf2/keap1 pathway and inhibition of the NFκB pathway ( Fang et al, 2022 ). Activation of AMPK and SIRT-1 has been shown to regulate hexokinase activity along with the regulation of glycolytic and mitochondrial energy metabolism ( Cantó et al, 2009 ; Ren et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides being a regulatory factor for energy status and glucose metabolism, it also plays a crucial role in regulating lipid metabolism, oxidative stress, and inflammatory responses ( Green et al, 2022 ). Fang et al have shown that these mitigative effects are achieved by activation of the Nrf2/keap1 pathway and inhibition of the NFκB pathway ( Fang et al, 2022 ). Activation of AMPK and SIRT-1 has been shown to regulate hexokinase activity along with the regulation of glycolytic and mitochondrial energy metabolism ( Cantó et al, 2009 ; Ren et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of AMPK to treat NAFLD has been established in numerous animal and preclinical studies. It has been shown that the levels of AMPK activation are substantially decreased in animals and patients with NAFLD, whereas the activation of AMPK by genetic manipulation, exercise, activators (e.g., A-769662, EX229/991, MT47-100), and mitochondria inhibitors (e.g., metformin) showed protective effects [ 12 , 13 , 14 , 15 , 16 , 17 ]. Researchers have demonstrated that the protection afforded by AMPK is related to its ability to act using different mechanisms, including improving peripheral insulin sensitivity; suppressing de novo lipogenesis and lipogenic genes (e.g., sterol regulatory element-binding protein 1 (SREBP-1c) and acetyl-CoA carboxylase (ACC-1)); and stimulating adipose tissue, liver fatty acid oxidation, and mitochondria integrity/function [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, studies on HIF-1α and AMPK regulation of lipid metabolism in NAFLD are mainly carried out in hepatocytes ( 89 , 90 ). The mechanisms by which lipid metabolism reprogramming in macrophages regulates autophagy are still poorly understood.…”
Section: Different Types Of Pcd and Lipid Metabolism In Macrophagesmentioning
confidence: 99%